HUBUNGAN POLA MAKAN DENGAN TEKANAN DARAH PADA ORANG DEWASA DI PERUMAHAN MUSTIKA BLOK H6 RT 05 RW 07 KABUPATEN TANGERANG - Era Delvi Agnes Savitri; Nanang Prasetyo Budi; Rina Puspita Sari (Nusantara Hasana Journal, 2021)
Eating patterns are the types of food consumed by a person with the content contained in fat, protein, carbohydrates, vitamins and minerals. Hypertension is high blood pressure that can be influenced by several factors such as diet, age, gender, and a salty diet. The purpose of this study was to determine the relationship between diet and blood pressure in adults. Research method correlation cross sectional approach the population in this study were adults in the Mustika Housing Block H6 RT 05 RW 07 Tangerang Regency as many as 50 respondents. Sampling technique with total sampling. The instruments used were questionnaire sheets, sphygmomanometer and stethoscope to measure blood pressure and observation sheets containing observation tables consisting of number, date of examination and results of measuring blood pressure. The results of the study, the data analysis used was univariate and bivariate analysis using the Spearman rank correlation. It was found that there was a correlation between diet and blood pressure in adults, as the results of the statistical test sig. (2-tailed) 0.001 < 0.05 with r 0.471 which means that there is a moderate relationship. Conclusion is that there is a significant between diet and blood pressure in adults with sig. (2-tailed) 0.001 < 0.05.